How Do Hospital Staffs Cope with Covid-19 at Work? A Phenomenological Study - Febrianto, Wahyu; Indriani, Wiwin; Dewanto, Aryo; -, Holipah (Jurnal Kedokteran Brawijaya)
The first confirmed Corona Virus Disease 2019 (Covid-19) case in Indonesia was found in March 2020 and rapidly spread out across all provinces. Covid-19 hit unexpectedly that almost all hospitals around the world were unprepared for it. Several studies show that Covid-19 impacts negatively on hospital finance, the mental health of healthcare workers (HCWs), and the death of HCWs. Hasta Brata Hospital (HBH) is one of the hospitals in East Java affected by the pandemic. Therefore, this study aims to investigate the experience of HBH staff face the issues. This study was qualitative research with a phenomenological approach. The data were collected using in-depth interviews with two HBHâ€™s staff. ACovid-19 pandemic causes problems to the hospital, especially the staff. They experienced deep emotional and physical pressure at work, such as fear of infection, repeated conflict with patient's visitor, having different mindsets among staff, and increasing workload. The situation in the community is also frustrating them as the Covid-19 cases keep rising, while people tend to disobey the Covid-19 prevention protocols. Fortunately, they have proper job resource, started from physical support such as the provision of personal protective equipment, nutritional enhancement, and periodic Covid-19 screening; cognitive support such as knowledge update about Covid-19 and its handling methods; to psychological support such as motivational and spiritual support from the HBH leader.Â Moreover, they also pose strong personal resources that help them to cope with stressful working situations. They could, then, bounce back, feel optimistic that they could fight against Covid-19, with the hope that the pandemic will have an end. Continuous spiritual support gives them another personal resource of tawakkal, an Islamic concept of giving entire resignation and reliance on God only after exerting maximum effort. It seems that job resources and personal resources have succeeded in reducing the highly demanding situation and transform it into positive outcomes. Given a challenging situation, the hospital staffs strive to perform well and bring themselves into their work when providing patient care. Covid-19 pandemic forced the hospital and staff to adapt to the condition quickly. The presence of job resources and the provision of strong personal resources have succeeded in moderating job demands and resulting in positive outcomes. Tawakkal becomes an adding point on staff's personal resources that made them realize that Covid-19 is inevitable, and they have to fight back before finally giving their full resignation to God.